Study of the structure and rheological and mechanical properties of silicone rubber/montmorillonite nanocomposites - Rabova, V. (Polimery, 2022)
This work is dealing with preparation of nanocomposites based on silicone rubber via: in situ polymerization of octamethylcyclotetrasiloxane in the presence of nanofillers and via homogenization of silicone rubber ?,?-dihydroxypolydimethylsiloxane with nanofillers on three-roll mill. After the preparation, the rheological properties, especially viscosity of the mixtures, were measured and after curing the mechanical properties (tensile strength) were studied. The structure of nanocomposites was described using XRD, WAXS and TEM methods.